Heat and mass transfer performance analysis and cooling capacity prediction of earth to air heat exchanger. (1st January 2015) - Niu, Fuxin; Yu, Yuebin; Yu, Daihong; Li, Haorong
Highlights: We investigated the performance and deduced a regression model for an EAHE. A one-dimensional steady-state control volume model was developed and applied. The model considered both heat and mass transfer in the tube and was calibrated. Six structural and operation factors were analyzed with the validated model. A polynomial regression model with high accuracy was developed. Abstract: A great portion of the primary energy is consumed by space heating and cooling in buildings. The need for utilizing more renewable energy in the building sector remains critical for ensuring the energy and environment sustainability. Geothermal energy is one of the renewable energy sources that we have an easy access to for supplying low-grade thermal energy with a low impact on the environment. The methods of utilizing geothermal energy for buildings include such as ground source heat pumps and earth to air heat exchangers (EAHEs). In this paper we presented the comprehensive performance analysis and deduced an easy-to-apply regression model for predicting the cooling capacity of an EAHE. A one-dimensional steady-state control volume model was developed and applied to simulate the performance of the EAHE. It couples both heat and mass transfer between the air and the tube. The model was calibrated by comparing against the experimental data from an existing renewable energy testing facility. After the calibration, six factors, namely the air temperature, the air relative humidity, the air velocity at the inlet of EAHE, the tube surface temperature, and the tube length and diameter on the performance were analyzed using the calibrated model. The polynomial regression models for predicting the cooling capacities including total, sensible and latent cooling capacity with high accuracy were obtained. The easy-to-apply formulas can be of great use in the design and application of EAHEs.